PENGARUH DANA BAGI HASIL, DANA ALOKASI KHUSUS, DANA DESA DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP KEMISKINAN DI KABUPATEN/KOTA DI INDONESIA - Rendy Alvaro; Ervita Luluk Zahara (Pusat Kajian Anggaran, 2019)
The study aims to analyze the effect of revenue sharing fund (DBH), special allocation fund (DAK), village fund, Gross Regional Domestic Product (GRDP) on poverty at the districts/city in Indonesia. Types of data use secondary data about revenue sharing fund (DBH), special allocation fund (DAK), village fund, Gross Regional Domestic Product (GRDP) in 2015-2018. Data analysis using panel data regression analysis. Result of research found that revenue sharing fund and special allocation fund had no significant effect on poverty. This study also proves village fund and Gross Regional Domestic Product (GRDP) have significant influence on poverty in Indonesia.